How non-specific low back pain affects gait kinematics: a systematic review and meta-analysis - Dal Farra, Fulvio; Lopomo, Nicola Francesco; Fascia, Matteo; Scalona, Emilia; Cerfoglio, Serena; Cimolin, Veronica (Frontiers in Pain Research, 2025)
BackgroundNon-specific low back pain (NS-LBP) is a is a highly prevalent musculoskeletal condition, with an estimated 619 million prevalent cases worldwide in 2020. Alterations in spinal and lower limb dynamics are considered as potential factors directly involved in this condition, thus we carried out a systematic review to summarize the evidence regarding walking kinematics in NS-LBP.MethodsThe reporting of this review followed the “2020 Preferred Reporting Items for Systematic Reviews and Meta-Analysis” (PRISMA 2020 checklist) and the protocol was preliminary registered in PROSPERO (ID: CRD42023431380). A search strategy was implemented in Medline, Embase, Scopus, Web of Science, and IEEE Xplore databases, up to March 2024. Inclusion criteria were: any analytical observational research instrumentally assessing the trunk and lower limbs kinematics of spontaneous walking in NS-LBP, in a comparison with healthy people. Study selection and data extraction were performed by two blinded reviewers, the methodological quality was evaluated by the Joanna Briggs Institute (JBI) Critical Appraisal Checklist and the quality of the evidence was rated through GRADE criteria.ResultsOverall, a total of 19 cross-sectional studies were included in this review and none of those was found without methodological issues. The meta-analysis showed a lower gait velocity [−15.42 (−22.78, −8.06) cm/s; p ≤ 0.0001], a lower cadence [−9.85 (−18.72, −0.99) steps/min; p = 0.03] and a lower step length [−6.30 (−11.83; −0.77) cm; p = 0.03] in NS-LBP. Regarding motion analysis, a few authors observed a less and asymmetrical motion of the lower spine in the frontal and in the transverse plane.ConclusionThere is very-low quality evidence that gait speed, cadence and step length are reduced in patients with NS-LBP. There is proof of a movement reduction in the lower lumbar spine and in the pelvis, both in the transverse and in the frontal plane. No differences in the lower limb kinematics was consistent over the studies.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42023431380.